Severe neurometabolic phenotype in npc1−/− zebrafish with a C-terminal mutation - Quelle-Regaldie, Ana; Gandoy-Fieiras, Nerea; Rodríguez-Villamayor, Paula; Maceiras, Sandra; Losada, Ana Paula; Folgueira, Mónica; Cabezas-Sáinz, Pablo; Barreiro-Iglesias, Antón; Villar-López, María; Quiroga-Berdeal, María Isabel; Sánchez, Laura; Sobrido, María Jesús (Frontiers in Molecular Neuroscience, 2023)
Niemann Pick disease type C (NPC) is an autosomal recessive neurodegenerative lysosomal disorder characterized by an accumulation of lipids in different organs. Clinical manifestations can start at any age and include hepatosplenomegaly, intellectual impairment, and cerebellar ataxia. NPC1 is the most common causal gene, with over 460 different mutations with heterogeneous pathological consequences. We generated a zebrafish NPC1 model by CRISPR/Cas9 carrying a homozygous mutation in exon 22, which encodes the end of the cysteine-rich luminal loop of the protein. This is the first zebrafish model with a mutation in this gene region, which is frequently involved in the human disease. We observed a high lethality in npc1 mutants, with all larvae dying before reaching the adult stage. Npc1 mutant larvae were smaller than wild type (wt) and their motor function was impaired. We observed vacuolar aggregations positive to cholesterol and sphingomyelin staining in the liver, intestine, renal tubules and cerebral gray matter of mutant larvae. RNAseq comparison between npc1 mutants and controls showed 284 differentially expressed genes, including genes with functions in neurodevelopment, lipid exchange and metabolism, muscle contraction, cytoskeleton, angiogenesis, and hematopoiesis. Lipidomic analysis revealed significant reduction of cholesteryl esters and increase of sphingomyelin in the mutants. Compared to previously available zebrafish models, our model seems to recapitulate better the early onset forms of the NPC disease. Thus, this new model of NPC will allow future research in the cellular and molecular causes/consequences of the disease and on the search for new treatments.